2020
DOI: 10.1149/1945-7111/ab754c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Current Density on Deposition of Ni-Mn3O4 Composite Coating and its High Temperature Behavior

Abstract: The combination of electrophoresis and electrodeposition technique is an effective method to increase Mn3O4 particle content in Ni-Mn3O4 composite coatings. The effect of current density during electrodeposition process on the deposition time, surface morphology, and Mn3O4 content of the composite coating has been systematically studied. Results show that the coatings deposited at a current density of 25 mA cm−2 for 4.5 min of deposition time are most suitable. Steels with composite coatings deposited under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…SEM photos reveal a decent degree of surface covering, however as the current density is increased to 35 mA/cm 2 , peeling is detected on the surface of the composite coating, which is consistent with prior research [29,41,42]. As the current density increases from 25 mA/cm 2 up to 35 mA/cm 2 , the amount of Co3O4 particles slightly decreases, and the amount of MnO2 particles in the coating increases gradually [43,44].…”
Section: Sem Analysissupporting
confidence: 89%
“…SEM photos reveal a decent degree of surface covering, however as the current density is increased to 35 mA/cm 2 , peeling is detected on the surface of the composite coating, which is consistent with prior research [29,41,42]. As the current density increases from 25 mA/cm 2 up to 35 mA/cm 2 , the amount of Co3O4 particles slightly decreases, and the amount of MnO2 particles in the coating increases gradually [43,44].…”
Section: Sem Analysissupporting
confidence: 89%
“…They found that Cr doping increases capacity and Na doping suppresses voltage-decay. Similar doping investigations using Mg, [24][25][26] Ni, [25][26][27][28][29][30][31][32][33][34][35] Co, 28,31,36,37 and N [38][39][40] on the electrode of lithium-ion batteries have demonstrated improved electrochemical performance.…”
mentioning
confidence: 80%